1993
DOI: 10.1093/jac/31.suppl_e.39
|View full text |Cite
|
Sign up to set email alerts
|

Selection of dose regimens of azithromycin

Abstract: The unique pharmacokinetics of azithromycin are characterized by high, sustained tissue concentrations. The concentrations of azithromycin were predicted, following various multiple dose regimens, from concentrations in tonsillar, prostatic, and uterine tissues following single oral doses. Following a five-day treatment regimen (500 mg on day 1, followed by 250 mg on days 2-5), or a three-day regimen (500 mg daily for three days), concentrations of azithromycin in tonsillar tissue, representative of respirator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0
2

Year Published

1995
1995
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(42 citation statements)
references
References 0 publications
1
39
0
2
Order By: Relevance
“…15 The long half-life allows for once-daily dosing, while sustained high-tissue concentrations for several days after dosing permit shorter-course therapy. 16 Once-daily azithromycin given over 5 days (30 mg/kg total dose) is as effective…”
Section: Introductionmentioning
confidence: 99%
“…15 The long half-life allows for once-daily dosing, while sustained high-tissue concentrations for several days after dosing permit shorter-course therapy. 16 Once-daily azithromycin given over 5 days (30 mg/kg total dose) is as effective…”
Section: Introductionmentioning
confidence: 99%
“…15,16 The preferential uptake by phagocytes leads to concentrations in infected tissues, which are much higher than in similar noninfected sites. 12 Another important property of azithromycin is that in tablet, suspension and sachet form it may be given without regard to meals, further enhancing the convenience of once-daily, short-duration dosing regimens.…”
Section: N B R I E Fmentioning
confidence: 99%
“…Concentration-versus-time curves feature high, sustained drug concentrations in tissues and comparatively low concentrations in serum ( Figure 5). 13 The prolonged elimination half-life (Ͼ60 hours) allows for once-daily dosing. 3 In a study of children with AOM, azithromycin 10 mg/kg administered on day 1 followed by 5 mg/kg on day 2 achieved mean peak middle-ear fluid concentrations of 8.6 and 9.4 µg/mL at 24 and 48 hours after the initial dose, respectively.…”
Section: Pharmacokinetic Support For Short-course Azithromycin Therapymentioning
confidence: 99%
“…Previous studies have shown a correlation between the serum and tissue PK of azithromycin. 13 Thus, a single, large dose may be preferable to multiple divided doses for achieving optimal tissue concentrations.…”
Section: Pharmacokinetic Support For Short-course Azithromycin Therapymentioning
confidence: 99%